Road safety environment around urban schools of Dharwad, India: a cross-sectional study - Shettar, Chidendra M.; Patil, Pushpa S. (International Journal Of Community Medicine And Public Health, 2017)
Background: India accounts to 10% of global road deaths. In 2013 around 1,40,000 people were killed and 5,00,000 were severely injured or disabled. Road traffic injuries (RTIs) are a major health problem among young people. Children are vulnerable road users and safety issues near school zones are the major cause of concern. Improper road safety measures can seriously affect the safeness and security of school children. In this context the study was conducted to observe road safety features in close vicinity around all schools in Dharwad city Karnataka, India. Methods:An observational study was carried out in Dharwad city focusing the safe environment around the 43 schools, which included both the government and the private schools. Data was collected from 1st April 2014 to 30th April 2014. All schools in the city were included for the study purpose. Results: Total 43 schools were observed for road safety features, we found that the road safety features and the safe environment around the schools were inadequate putting children at risk. Conclusions:We concluded that there is a need for immediate action and the responsible local authorities should take up this issue as top priority and implement the corrective road safety measures for the health of school children.